(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Utilizing intraoral scanners and laboratory/chairside milling devices to make dental restorations and appliances from numerous materials including wax, metals, composite resins, and ceramics, CAD/CAM in dentistry is expanding and becoming more user- and patient-friendly. Aim’s & Objectives: When accessible, the various qualities and precision of CAD/CAM materials are compared to those of conventional materials/methods in order to evaluate the CAD/CAM materials. Methods & Materials: The properties of these materials may differ from those of conventional and additively manufactured restorations. Understanding the distinctions between these qualities is crucial for selecting materials and fabrication techniques. In a growing number of contexts, additive manufacturing is replacing subtractive manufacturing. However, neither the chemical composition nor the mechanical and physical properties of these materials have yet been determined. The therapeutic efficacy of 3D-printed products requires a great amount of study and time. Conclusion: The present advancements and potential applications of CAD/CAM technology are exciting and revolutionising restorative dentistry. Before making definitive claims and judgements to replace traditionally created materials, it is of the utmost importance to guarantee that the various materials have been subjected to adequate testing and evaluation. Clinical Significance: CAD/CAM materials are adaptable and quickly becoming the material of choice for a variety of dental restorations and appliances. Before suggesting recently launched CAD/CAM materials for patient care, it is necessary to ensure that adequate clinical and research-based information demonstrating the success and longevity of these materials is available.